Optimisation of ducted fans with CFD - Biava, M.; Carrión, M.; Steijl, R.; Barakos, G.N.; Stewart,D. (My University, 2015)
This paper presents the performance analysis and design of a ducted propeller for lighter-than-air vehicles. Highfidelity CFD simulations were undertaken on a model with simplified geometry to quantify the effect of the duct, and to assess the influence of the blade twist on the ducted propeller performance. It is shown that the duct is particularly effective for low speed operations, and that the blades with relatively high twist have better performance over a wide range of operating conditions. Design of the optimal twist distribution was then attempted, by coupling the flow solver with a quasi-Newton optimisation method. Flow gradients were provided by a fully implicit adjoint solver for the RANS equations, which accounts for the turbulence model coupling. Results show a 2% reduction in the required power of the optimised ducted propeller. The degree of approximation introduced by the simplified geometry was also quantified, by solving the flow for a more realistic geometry and through comparison with available experimental data.
Keywords: Aerodynamics